The Influence of Competence and Motivation on Employee Performance at BKPSDM Bandung City - Hidayat, Yadi Feriadi; Kurhayadi, Kurhayadi; Sahromi, Sahromi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
This research aims to find out whether competence and motivation influence employee performance at BKPSDM Bandung City. The independent variables are competence and motivation, and the dependent variable is employee performance. This type of research is included in quantitative research. The research methods used are descriptive and verification methods. The population in this research is employees at BKPSDM Bandung City, totaling 103 people. The sampling technique is probability sampling using simple random sampling, while to calculate the number of samples using the Slovin formula with a significance level of 5%, so the total sample is 82 employees at BKPSDM Bandung City. The data analysis used in this research is multiple linear regression analysis using SPSS software. Partial and simultaneous research results show that competence and motivation influence employee performance at BKPSDM Bandung City. The magnitude of the influence of competence and motivation on employee performance is 62.5%.